2005
DOI: 10.1111/j.1745-7262.2005.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens in males: what have we learned in the last 10 years?

Abstract: This review focuses on the role of estrogen in men, mainly in male reproduction. The continuing increase in data obtained, and recent discoveries in this area will enable a better understanding of male physiology; these, in turn, will have important clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 199 publications
(335 reference statements)
5
77
0
5
Order By: Relevance
“…The role of estrogens (ES) in regulation of male reproductive functions and testicular development is widely accepted [95]; however the molecular mechanism of their physiological role in spermatogenesis is not clearly defined. The ES signaling is known to be mediated by at least two functional isoforms of estrogen receptors (ER) known as ERα and ERβ that are encoded by two different genes on the long arm of chromosomes six (6q25) and 14 (14q23-24), respectively [22].…”
Section: The Estrogen Receptors (Esr) Genes Mutationsmentioning
confidence: 99%
“…The role of estrogens (ES) in regulation of male reproductive functions and testicular development is widely accepted [95]; however the molecular mechanism of their physiological role in spermatogenesis is not clearly defined. The ES signaling is known to be mediated by at least two functional isoforms of estrogen receptors (ER) known as ERα and ERβ that are encoded by two different genes on the long arm of chromosomes six (6q25) and 14 (14q23-24), respectively [22].…”
Section: The Estrogen Receptors (Esr) Genes Mutationsmentioning
confidence: 99%
“…28,29 Indeed, previous studies have suggested a role for aromatase in sperm motility. Men with an aromatase deficiency 30 and aromatase knockout mice 31 have been reported to have decreased sperm motility, whereas aromatase activity has been found to be 50% greater in motile compared to immotile spermatozoa. 32 In addition, the amount of P450 aromatase transcripts was found to be 30% lower in immotile versus motile spermatozoa of healthy men, 33 and a twofold decrease in aromatase transcripts was observed in spermatozoa from a group of infertile men.…”
Section: 27mentioning
confidence: 99%
“…Oestrogen has been reported to have a significantly negative effect on sexual behaviour and ultimately results in decreased intracavernosal pressure and nitric oxide-mediated cavernosal smooth muscle relaxation. 16,17 In addition, the action of E 2 through a non-genomic mechanism has been reported in which E 2 can modulate the cell surface and influence ionic channels as a part of the tissue response. 18 Although the elevated E 2 levels in ageing males may act as a risk factor for ED, 9 the causeeffect relationship is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach's alpha coefficient has also indicated a high internal consistency. 12,13 Scoring the IIEF domain of erectile function allowed the classification of each patient as having no (26)(27)(28)(29)(30), mild (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (11)(12)(13)(14)(15)(16) or severe (0-10) ED. At the same visits during which they were assessed for ED, all patients were also interviewed to gather their sociodemographic characteristics and relevant medical history.…”
Section: Ed Assessmentmentioning
confidence: 99%